Recurrence Methods for Communication Data, Reflecting on 20 Years of Progress - Angus, Daniel (Frontiers in Applied Mathematics and Statistics, 2019)
Conversational interaction is a complex, interactive, dynamic and multimodal activity, allowing us to transmit and receive information, to form and maintain social ties, and also perform many other cultural and ritualistic functions. Methodologies for studying conversation, and human discourse in general, vary across many levels of abstraction, with everything from the qualitative manual coding methods of Conversation Analysis, through to the quantitative processing and analysis of vocal qualities based on frequency spectra. In this review we focus on how the paired techniques of recurrence plotting and recurrence quantification analysis (RQA) have been utilised in the study of human discourse. We focus on recurrence analyses that have examined communication behaviours and activities in various institutional and social settings. Our review focusses along several key dimensions: discourse type, the role of time in the encoding of input data, and the challenges that multi-modality place on recurrence-based discourse analysis methods. We argue that recurrence analysis holds much promise for the ongoing study of discourse, and that its full potential has yet to be realised within this domain of application.